KEANEKARAGAMAN JENIS TUMBUHAN MASA LAMPAU DI SITUS PEMUTERAN, KABUPATEN BULELENG, PROVINSI BALI (Kajian berdasarkan analisis palinology) - Vita Vita (Berkala Arkeologi, 2011)
A variety of plant species that exist today reflect the diversity of plant species as well as how pre-existing or in the past, the area along the environmental conditions are not much changed significantly. Plant communities in a region will illustrate the diversity of plant species tolerant to environmental conditions in the area. The power plant tolerance to different environmental factors will lead to different types of plants that live in the area By using HF method and Acetolysis, then the results of the identification of fossil pollen (pollen analysis) that has been done specifically on a sample of soil /sediment from the findings of pottery, as well as the box has been opened at the excavation site Pemuteran, Buleleng Regency, Bali Province randomly, especially in layer B in test pit 4 and 5, the types derived from fossil pollen from plants derived from plants that are useful in the family Compositae, Poaceae, Malvaceae and Papilionaceae. In addition, there is also a pollen that is not available on the site around Pemuteran, such as the family Pinaceae, Fagaceae, Daphnae, Sequoia, Geraniaceae, Cupressus.